Salmonella spp. in Pet Reptiles in Portugal: Prevalence and Chlorhexidine Gluconate Antimicrobial Efficacy - João B. Cota; Ana C. Carvalho; Inês Dias; Ana Reisinho; Fernando Bernardo; Manuela Oliveira (Antibiotics, 2021)
A fraction of human Salmonella infections is associated with direct contact with reptiles, yet the number of reptile-associated Salmonellosis cases are believed to be underestimated. Existing data on Salmonella spp. transmission by reptiles in Portugal is extremely scarce. The aim of the present work was to evaluate the prevalence of Salmonella spp. in pet reptiles (snakes, turtles, and lizards), as well as evaluate the isolates’ antimicrobial resistance and virulence profiles, including their ability to form biofilm in the air-liquid interface. Additionally, the antimicrobial effect of chlorhexidine gluconate on the isolates was tested. Salmonella was isolated in 41% of the animals sampled and isolates revealed low levels of antimicrobial resistance. Hemolytic and lypolytic phenotypes were detected in all isolates. The majority (90.63%) of the Salmonella isolates were positive for the formation of pellicle in the air-liquid interface. Results indicate chlorhexidine gluconate is an effective antimicrobial agent, against the isolates in both their planktonic and biofilm forms, demonstrating a bactericidal effect in 84.37% of the Salmonella isolates. This study highlights the possible role of pet reptiles in the transmission of non-typhoidal Salmonella to humans, a serious and increasingly relevant route of exposure in the Salmonella public health framework.